2009
DOI: 10.1063/1.3093680
|View full text |Cite
|
Sign up to set email alerts
|

Multiwalled carbon nanotube films as small-sized temperature sensors

Abstract: We present the fabrication of thick and dense carbon nanotube networks in the form of freestanding films (CNTFs) and the study of their electric resistance as a function of the temperature, from 4 to 420 K. A nonmetallic behavior with a monotonic R(T)R(T) and a temperature coefficient of resistance around −7×10−4 K−1−7×10−4 K−1 is generally observed. A behavioral accordance of the CNTF conductance with the temperature measured by a solid-state thermistor (ZnNO, Si, or Pt) is demonstrated, suggesting the possib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
72
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(79 citation statements)
references
References 25 publications
7
72
0
Order By: Relevance
“…However, the greatest slope for the sample transferred at 20 mN m − 1 was observed. The linear decrease of the MWCNT resistance was also observed in this temperature range [28] and confirms the tunneling conduction mechanism as dominant over the pure metallic conduction. The temperature coefficients of resistance (TCR) defined as:…”
Section: Electrical Propertiessupporting
confidence: 65%
“…However, the greatest slope for the sample transferred at 20 mN m − 1 was observed. The linear decrease of the MWCNT resistance was also observed in this temperature range [28] and confirms the tunneling conduction mechanism as dominant over the pure metallic conduction. The temperature coefficients of resistance (TCR) defined as:…”
Section: Electrical Propertiessupporting
confidence: 65%
“…The temperature coefficients of Figure 2a were calculated according to equation S = Δ I /(Δ T · I FS ), where Δ T is the variation of temperature, Δ I is the variation of I c , and I FS is the full scale range of I c . The highest coefficient S max was obtained as 0.04 K −1 at 100 °C and 24 V U e (Table 1), higher than the values of other reported CNT-based temperature sensors [1,2,3,4,5]. …”
Section: Resultsmentioning
confidence: 58%
“…The development goal of a temperature sensor usually includes high sensitivity, small footprint, and low power consumption. The potential of a carbon nanotubes (CNTs) based temperature sensor offers great opportunities towards extreme miniaturization and low power consumption [1,2,3,4,5], thanks to the unique nanoscale structure and electrical property [6,7,8,9,10,11]. Recent studies showed that CNTs could be used to construct temperature sensors.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Their incorporation into polymeric matrices originate nanostructured materials showing new properties [8][9][10]. The fact that CNTs with either semiconducting or metallic character showed an electric resistance strictly dependent on temperature made them interesting for the realization of small-sized temperature sensors [11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%